Wage Flexibility and Economic Performance : Evidence Across Industrial Countries - Kandil, Magda (IMF Working Papers; Working Paper, 2000)
This paper provides new empirical evidence on the degree of nominal wage flexibility in a sample of nineteen industrial countries. Across countries, aggregate uncertainty increases the degree of wage flexibility in the face of various shocks. Wage flexibility stabilizes fluctuations in real output and guarantees workers a higher real standard of living in response to aggregate demand shocks. Wage flexibility in response to energy price shocks guarantees workers higher real wages without exacerbating price inflation or output contraction. Nominal wage inflation decreases in response to productivity shocks, reinforcing output expansion.